Analisis Perilaku Keselamatan Mengemudi (Safety Driving) Pada Sopir Bus PO X Slawi Tegal - Desta Windafasa, Nener; -, Ekawati; Kurniawan, Bina (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2011)
Traffic is a major factor supporting the productivity of labor, so we must realize the potential hazards of traffic in order to prevent traffic accidents. Road traffic accidents can be controlled with the implementation of safety driving and training of safety driving. The purpose of this study were analysis of predisposing factors, enabling factors and reinforcing factors of bus driver behavior to apply safety driving at PO X. This study used qualitative research with an interpretive approach. The subjects of this research were main director, board manager and bus driver. Sources of primary data obtained from in-depth interviews and observation. Data analysis used descriptive content analysis. This research shows that the road traffic accidents in the PO X controlled by safety driving training of the bus driver. Predisposing factors were knowledge, attitudes, belief of safety driving benefit and appraisal about safety driving. Enabling factors were the availability of personal protective equipment and the integrity of the machine, regulations and penalties on implementation of safety driving and additional knowledge of safety driving. Reinforcing factors of safety driving implementation were board manager and main director. Conclusion of this study is the behavior of drivers depends on themselves and superior’s behaviour.